Efek Diversifikasi Pembiayaan Sektor Ekonomi Terhadap Profitabilitas Dan Risiko Bank Syariah Di Indonesia - Muhammad Khozin Ahyar (JPS (Jurnal Perbankan Syariah), 2021)
Financing in Islamic banking can be regarded as an investment because Islamic banking is a fund manager (mudharib) from the owner of the funds (shahibul maal), namely the customer. This research aims to show that investment diversification can minimize risk and increase profitability in Islamic banking. This study uses a quantitative method with a multiple linear regression model with 14 independent and 2 dependent variables. The data used is secondary data obtained from the Islamic banking statistics of the Financial Services Authority. The result of this research is that diversification of financing based on the economic sector has no effect on profitability but affects risk in reducing default. This research has implications for reducing the risk of default in Islamic banking, marked by the performance and quality of Islamic banking financing getting better.